Culinary tourism and post-pandemic travel: Ecosystem responses to an external shock - Pauline A. Milwood; Anne P. Crick (Journal of Tourism, Heritage & Services Marketing, 2021)
Purpose: The COVID-19 (SARS-CoV-2) global pandemic forced hospitality and tourism service providers to respond by pivoting business models in line with governmental restrictions to curb the spread of the virus. This paper explores the online responsiveness of tourism-affiliated culinary service providers to a major external disruption. Methods: This study uses ecosystem resilience and Internet marketing theories to analyze 139 web homepages of culinary tourism service providers promoted by the official tourism website of Jamaica, to measure of Jamaica to measure online responsiveness to the COVID-19 pandemic. Results: Findings show that web page responses vary between the official tourism web page and the restaurants promoted on its site. Responses also vary across restaurant affiliation clusters and across location clusters. Further, resilient web page responses are more commonly associated with hotel restaurants and eponymous restaurants. Implications: Culinary service providers promoted by the official tourism marketing arm of a destination should consistently practice resilient online marketing response to external shocks. This study provides a novel analysis of online responsiveness to COVID-19 and contributes a summary framework for resilient response by culinary ecosystem providers preparing for post-pandemic travel.
Keywords: H12; L66; R41; 330; culinary tourism; COVID-19; ecosystems; external shock; Jamaica; resilient